2006
DOI: 10.2510/376823
|View full text |Cite
|
Sign up to set email alerts
|

Instability of Public Health Insurance Coverage for Children and Their Families: Causes, Consequences, and Remedies

Abstract: This report examines the extent, causes, and consequences of instability in public coverage programs for children and families. It focuses particularly on the phenomenon of "churning," which occurs when individuals lose and regain coverage in a short period of time. It also looks at strategies to make public program coverage more stable for children and families. Findings are drawn from a variety of sources, including national and state-based studies, roundtable discussions and interviews with stakeholders and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 37 publications
1
23
0
1
Order By: Relevance
“…20 However, states do not always pursue these strategies, or they might abandon or curtail them when state budgets are under pressure, because effective strategies will result in additional coverage costs. 21 This is a particular problem for Medicaid, given that the federal government pays a lower share of coverage costs compared with its payments to SCHIP.…”
Section: Issues Affecting Medicaid's Ability To Serve Children Over Tmentioning
confidence: 99%
“…20 However, states do not always pursue these strategies, or they might abandon or curtail them when state budgets are under pressure, because effective strategies will result in additional coverage costs. 21 This is a particular problem for Medicaid, given that the federal government pays a lower share of coverage costs compared with its payments to SCHIP.…”
Section: Issues Affecting Medicaid's Ability To Serve Children Over Tmentioning
confidence: 99%
“…2126 La Veist et al showed that mistrust toward health care organizations leads to failure to take medical advice and to keep follow-up appointments, 27 while Brookhart et al showed that provider continuity is positively associated with medical adherence. 28 Given that medical mistrust and lack of provider continuity are thought to be more common among racial minorities and low-income populations, 25,2932 their potential role in the observed cancer mortality disparities among these groups should be explored.…”
mentioning
confidence: 99%
“…16,17 From the authors' extensive ongoing interactions with Medicaid and CHIP officials, it seems that many more states would like to measure performance on this dimension, both for its utility in assessing enrollment efforts and because continuous enrollment is a prerequisite for valid measurement of quality of care. 18 Availability of services also is included in CHIPRA specifications for the initial core set of pediatric quality measures, and the NASHP survey reflects considerable state concern in this area. Roughly two thirds of states reported inadequate provider capacity in either or both of their S-CHIP or M-CHIP programs.…”
Section: Discussionmentioning
confidence: 99%